2019
DOI: 10.1088/1361-6501/ab4488
|View full text |Cite
|
Sign up to set email alerts
|

K-SVD-based WVD enhancement algorithm for planetary gearbox fault diagnosis under a CNN framework

Abstract: This paper presents a new method of planetary gearbox fault diagnosis by dealing with and analyzing vibration signals. This study contributes to the realization of automatic diagnosis using a convolution neural network (CNN) to process time-frequency distributions (TFDs) transformed from vibration time series. In order to solve the problem of non-stationary working states and strong noise interference in industrial applications, a K-singular value decomposition (K-SVD) is used to enhance the resolution of TFDs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…The data-driven methods based on time-frequency analysis are also an effective tool for extracting mechanical health information from nonstationary signals [6]. Traditional time-frequency analysis methods, such as wavelet transform [7], Wigner-Ville distribution [8], and short-time Fourier transform [9], have made certain achievements in bearing fault diagnosis. However, these methods lack self-adaptive capability when processing bearing vibration signals for fault diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…The data-driven methods based on time-frequency analysis are also an effective tool for extracting mechanical health information from nonstationary signals [6]. Traditional time-frequency analysis methods, such as wavelet transform [7], Wigner-Ville distribution [8], and short-time Fourier transform [9], have made certain achievements in bearing fault diagnosis. However, these methods lack self-adaptive capability when processing bearing vibration signals for fault diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Fan and Zhu [28] used EMD and SVD to process vibration signals and achieved a satisfied effect in removing noise interference. Considering the unstable operating condition in industrial applications and the noise, Li et al [29] put forward a new method for planetary gear box fault diagnosis, using the singular value decomposition (SVD) to enhance the resolution of the TFD obtained by the Wigner-Ville distribution (WVD). e results showed that the proposed method can not only reduce the influence of the cross terms of WVD but also eliminate noise and improve the accuracy of fault diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Because the vibration signal of the cylinder head is affected by noise and other disturbances, before extracting the degraded features, we need to preprocess the source signal to restore the actual signal. Nowadays, Wigner–Ville distribution (Li et al, 2020), wavelet transform (El-Hendawi and Wang, 2020), and empirical mode decomposition (EMD) (Cai et al, 2020) are commonly used filtering methods. Different from other methods because its basic function is decomposed by the data itself, empirical mode decomposition (EMD) has the advantages of intuitive, direct, posterior, and adaptive.…”
Section: Introductionmentioning
confidence: 99%